Comunication media: effects, cognition and intermediation - Flor Arbulú, Marcia De la (1994)
Reviewing the different theories about che comprehension of mass media effects, this article tries to explain the interaction arnong the media. cognition and learning. The synrhesis of different aspects of the intermediation are also described including the parents' and teachers' role in the process. The situation of mass media in Peru is briefly discussed.